Transaction Cost, Price Risk Perspective and Marketing Channel Decision of Small-Scale Chili Farmers in Tra Vinh Province, Vietnam - Hung, Pham Quoc; Khai, Huynh Viet (Asian Journal of Agriculture and Rural Development, 2020)
The aim of this study is to determine the marketing channel and the factors affecting farmer’s selection of a distribution channel of chili produced in Tra Vinh province, Vietnam. With primary data of 193 chili farmers, the study based on the theory of transaction cost economics to estimate the determinants of marketing channels using the approach of the Probit model. The results showed that the marketing choice decision of chili farmers was affected by transaction costs, price risk attitude and farmers’ characteristics. Cooperatives mainly used seedling supply as an interlocked exchange to encourage farmers to remain in the cooperative channel. The finding also revealed that cooperative channel was not just the preferred channel when farmers were confronted with selling pressure due to the perishable nature of the chili, but also was a safe channel for more risk-averse farmers.